Management of Semilleros in the area of Language Teacher training: a comparative study (2024)
Research Incubators are spaces for formative research with voluntary participation by students and coordinating teachers. They are important components in the research schemes of universities and are fundamental in the field of teacher training of any discipline. This paper intends to know the factors associated with educational management that affect the permanence of the Research Incubators in the area of language teacher training, in three universities in the department of Antioquia (Colombia). Using a qualitative research strategy and through a multiple case study, a group of nine participants, made up of students, coordinating teachers of research incubators and administrative staff were interviewed to know their perceptions about the factors that affect their management. The results highlight the importance of the articulation of endogenous and exogenous factors for the correct functioning of the research incubators, among which motivation, affectivity, participation in knowledge networks, and institutional funding, among others, stand out. In addition, conclusions and recommendations are presented for improving the management processes of these formative research spaces both internally and at an institutional level.